ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF THE DEVELOPMENT OF AGRICULTURAL ACTIVITIES OF COMMUNAL ENTERPRISES IN THE FORMATION OF LOCAL FOOD SECURITY - Shpykuliak , O. H.; Shelenko , D. I.; Sukhovii , A. I. (The actual problems of regional economy development, 2024)
The organizational, economic and institutional characteristics, the essence of communal entrepreneurship are defined, the peculiarities of the functioning of communal enterprises as leaders of the entrepreneurial interests of territorial communities are outlined. It has been proven that communal agrarian entrepreneurship is a functional management, which is aimed at obtaining economic, social, and institutional benefits of territorial communities. The institutional characteristics and organizational and economic functionality of communal enterprises in agricultural activity are given. There is a well-founded need for investment in the development of the mechanism of management (entrepreneurship) of individual territorial communities of Ukraine. Institutional characteristics and organizational and economic functionality of communal enterprises in the agricultural sector of the economy of Ukraine have been proposed. The features of the support program from "U-LEAD with Europe", which is focused on the creation of joint utility companies and will facilitate the completion of the course on the creation of a joint utility company, have been revealed. Peculiarities of the development of communal agricultural enterprises are studied. The agricultural activities of communal enterprises of territorial communities in Poltava and Ivano-Frankivsk regions and other regions of Ukraine are given as examples, with assessments of their potential participation in the formation of food security at the local level. The investment aspects of the development of communal entrepreneurship of territorial communities in the rural business sector are characterized. The institutional characteristics of the formation of structures of communal status, of the organization of processing of agricultural products and waste from their production are determined, which is practically correlated with the possibilities of development of agricultural activities of communal enterprises. The priorities and prospects for the development of communal enterprises in the production of agricultural products as a mechanism for implementing the initiatives of territorial communities in the formation of guarantees of local food security have been outlined.